Pengembangan Modul Zoologi Vertebrata Terintegrasi Scientific Inquiry - Wachidatul Linda Yuhanna; Raras Setyo Retno (Universitas Sebelas Maret, 2018)
This study aims to develop vertebrate zoological modules that are integrated with scientific inquiry. Method in this study is Research and Development (R&D) which refers to ADDIE (Analyze, Design, Develop, Implementation, and Evaluate). This study used 2 validators and 10 students for small-scale trials. The results show that in the requirement analysis phase, students need modules that match the characteristics of learning in theory and practice. The desired module is a module that can assist in the process of understanding the material and practicum. Design stage includes content design and layout. The contents consist of 8 chapters namely introduction, Zoological Classification, Taxonomy of Vertebrate, Pisces, Amphibians, Reptiles, Mammals and Aves. Layouts are arranged attractively and interactively in each chapter. Development stage consists of integrating the scientific inquiry into the module. Expert validation shows that module of zoologyvertebrate integrated by scientific inquiry is feasible to use. Implementing stage with small-scale test show that this module is also feasible to use. The evaluation phase contains inputs and suggestions for module improvements.